Why Do Women Talk About It? Reasons for Disclosure of Sexual Victimization and Associated Symptomology. (December 2021) - Carson, Kaitlin Walsh; Babad, Sara; Brown, Elissa J.; Nikulina, Valentina
Many sexual victimization survivors disclose their experience; however, there is limited research investigating why women disclose this experience and how reasons relate to psychopathology. The current online study aims to further understand the experiences of 142 female survivors (aged 18–29 years) by identifying their reason for disclosure and investigating how reasons relate to self-reported depression and post-traumatic stress disorder (PTSD) symptomology. Qualitative analyses identified two reasons: intentional and elicited disclosures. Hierarchical linear regressions revealed that elicited disclosures were associated with higher PTSD symptomology than intentional disclosures above and beyond relevant covariates, suggesting that disclosure reason is an important factor in the recovery process.